2001
DOI: 10.1093/qjmed/94.9.485
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress in Alzheimer's disease as assessed with 4-hydroxynonenal but not malondialdehyde

Abstract: Oxidative stress is thought to play a major role in the pathogenesis of Alzheimer's disease (AD). Although there is strong post-mortem and experimental evidence of oxidative damage occurring in AD brains, the use of markers in the peripheral circulation to show oxidative stress is less convincing. We examined plasma from AD patients for markers of increased oxidative stress. We report elevated levels of 4-hydroxy-nonenal (4-HNE) in AD patients compared to controls (median 20.6, IQR 6.0-25.2 vs. 7.8, 3.3-14.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(145 citation statements)
references
References 36 publications
5
137
0
3
Order By: Relevance
“…Both vascular dementia and AD were variably associated with reduced serum or plasma levels of vitamins A, C, and E, even when controlled for nutritional status. [83][84][85][86][87] Although vitamin E delayed progression of AD in one clinical study, 88 antioxidant vitamin supplementation did not affect incident cognitive impairment over 5 years, as a secondary outcome of a large placebo-controlled cardiac study involving 20,536 individuals. 89 …”
Section: Antioxidant Levelsmentioning
confidence: 96%
“…Both vascular dementia and AD were variably associated with reduced serum or plasma levels of vitamins A, C, and E, even when controlled for nutritional status. [83][84][85][86][87] Although vitamin E delayed progression of AD in one clinical study, 88 antioxidant vitamin supplementation did not affect incident cognitive impairment over 5 years, as a secondary outcome of a large placebo-controlled cardiac study involving 20,536 individuals. 89 …”
Section: Antioxidant Levelsmentioning
confidence: 96%
“…Such pathogenic alterations are regarded as clues to the cause of AD, particularly changes in neuronal cell metabolism such as the oxidation of proteins and DNA, lipid peroxidation, the formation of free radicals, the progression of neuritic injury by ß-amyloid (Aß), the disruption of neuronal metabolic homeostasis and neuronal cell death (1)(2)(3). The neurotoxicity of Aß, a major component of AD pathogenesis, has been suggested to induce neuronal degeneration and death by rendering neurons vulnerable to increases in oxidative stress and impairing cellular metabolism (4).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we quantified the accumulation of Aβ40. A standard peptide and the samples were incubated in microplates coated with the monoclonal antibody BNT77, which recognizes human and rat Aβ (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), for 1 h at 4°C. After washing five times, the plates were incubated with an HRP-conjugated antibody raised against the C-terminus of Aβ40 for 1 h at 4°C.…”
Section: )mentioning
confidence: 99%
“…2,3) A byproduct of lipid peroxidation, 4-hydroxynonenal (4-HNE) is thought to play central roles in diseases such as AD 4,5) and Down syndrome. 6) 4-HNE is composed of ω-6 polyunsaturated fatty acids, 7) and its levels were found to be increased in AD patients' brains [8][9][10] and plasma 11) compared with age-matched healthy individuals. Previous report showed that amyloid β induced oxidative stress in the cultured hippocampal neurons and Caenorhabditis elegans.…”
mentioning
confidence: 96%